Pengaruh Effortfull Swallow Manuver terhadap Peningkatan Fungsi Menelan pada Pasien Disfagia Paska Stroke di Rumah Sakit Umum Pusat Nasional Dr Cipto Mangunkusumo Jakarta - Sawiroh, Yoyoh; Mangunsong, Roy Romey Daulas (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Dysphagia is one of the complications that often occurs in stroke patients, which has long-term effects such as dehydration, malnutrition, and aspiration pneumonia, thereby affecting poor quality of life. Objectives: This study aims to determine the effect of the effortful swallow maneuver on improving swallowing function in post-stroke dysphagia patients at Dr. Cipto Mangunkusumo National General Hospital in Jakarta. Methods: This study was a quantitative study with a “One Group Pre-test and Post-test” research design. Statistical tests used the McNemar Test and Pearson's correlation test. The number of respondents in this study was 15 dysphagia outpatients at the Medical Rehabilitation Unit of Dr. Cipto Mangunkusumo National General Hospital in Jakarta. The research instrument used to measure swallowing function was the Toronto Bedside Swallowing Screening Test (TOR-BSST). Results: Before the intervention, 12 respondents were unable to swallow and 3 respondents were able to swallow. After the intervention, 2 respondents were unable to swallow and 13 respondents were able to swallow. There was a significant difference in the swallowing function of respondents before and after the Effortful Swallow Maneuver intervention based on the results of the McNemar Test analysis with a significance value of 0.002. There was a strong and positive correlation between the Effortful Swallow Maneuver and swallowing function based on the results of the Pearson correlation test with a result of 0.705.  Conclusion: The Effortful Swallow Maneuver has an effect on improving swallowing function in post-stroke dysphagia patients at Dr. Cipto Mangunkusumo National General Hospital in Jakarta. Keywords: Dysphagia, Effortfull Swallow, Manuver